Evaluasi Kapabilitas Tata Kelola SIMPEG STITEK Bontang Berbasis COBIT 5 - Belva Pranama Sriwibowo; Irfani Zuhrufillah; Muhammad Ammar Alfarabi; Muhammad Yusuf Saputra (Universitas Harapan Bangsa, 2026)
This study aims to evaluate the capability level of information technology governance in the personnel information system (SIMPEG) of STITEK Bontang using the COBIT 5 framework. The evaluation focuses on the domains of APO07 (Manage Human Resources), DSS01 (Manage Operations), DSS05 (Manage Security Services), and MEA01 (Monitor, Evaluate, and Assess Performance and Conformance), which are critical to service continuity and system risk management. The research methodology includes a literature review, data collection through questionnaires and interviews, and process capability analysis based on the COBIT 5 assessment model. Capability values are calculated by averaging indicator achievement scores for each domain and compared with the target capability levels to identify existing gaps. The results indicate that the average capability level of STITEK Bontang’s SIMPEG is Level 2.2 (Managed Process). Operationally, the system performs reliably with routine backup activities and no significant security incidents have been recorded. However, the gap analysis reveals weaknesses in process formalization, particularly in documentation, standard operating procedures, and evidence-based evaluation mechanisms. This study recommends the development of formal standard operating procedures, technical documentation, and strengthened monitoring and evaluation practices to improve IT governance capability to Level 3 (Established).